Differential diagnosis of psychotropic side effects and symptoms and signs of psychiatric disorders - Mihanović, Mate, liječnik (Array, 2009)
Unrecognising and undistinguishing of psychotropicinduced side effects from psychopathological phenomena and/or physical signs which are, according to relevant classification criteria, standard parts of psychiatric disorders, most frequently can cause increase the dose of the psychotropic medication, assigning of the unwarranted diagnoses, and/or addition of unnecessary medications. Some of the most frequent side effects that can be caused by the diagnostic difficulties and/or misjudgements of the phenomenological recognition and differentiating side effects from psychiatric symptoms and signs are: druginduced akathisia, intensive anticholinergic pharmacodynamic effects including delirium, neuroleptic induced Parkinsonism, paradoxically antidepressants-induced worsening or re-emerging depression, acute dystonia and tardive dyskinesia and others